Opportunities and Challenges in Maintaining the Balance Between Accessibility and Security in the Final Theses of Students From the Information Services Study Field - Poceviciene, Rasa (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2025)
Today's information services are essentially related to access to content, various data, statistics, especially relevant for the development and implementation of various strategies and/or tactics, which are often very important for the future development of any organization. Nowadays, they are also user-centric (individual or organizations), which means knowing the user's needs, expectations, features, characteristics, etc. Increasingly, we are not just talking, but implementing an evidence-based approach that sometimes requires highly sensitive or reliable data. In all these situations, we should maintain a balance between accessibility and security, as well as in the study process. This is especially evident in the final theses of students studying Information Services. Šiauliai State University of Applied Sciences, as well as all universities of applied sciences and the applied research conducted in them, are intended to solve real problems of real organizations, when it is not so easy to ensure access to complete and comprehensive information and to make optimal decisions based on it, but at the same time to maintain confidentiality and protection of data sensitive to the organization or individual. The report will present the experience of the Šiauliai State University of Applied Sciences and the challenges that arise when preparing students' theses in this field of study.